(untitled) (Research, Society and Development, 2023)
Botulinum toxin is a therapeutic substance widely used in dentistry, especially in the area of ​​orofacial harmonization. In orofacial harmonization procedures, botulinum toxin has proven to be an effective treatment in treating facial asymmetries, perioral wrinkles and relieving bruxism. Furthermore, its potential to relax the chewing muscles can contribute to the reduction of chronic facial pain and temporomandibular disorders, improving patients’ quality of life. However, it is essential that such procedures are carried out by qualified professionals to ensure safety and effectiveness. Bruxism, in turn, is a neuromuscular disorder characterized by the involuntary clenching or grinding of teeth, mainly during sleep, but also during the day. Its multifactorial etiology and clinical implications that go beyond dental health, such as headaches, temporomandibular disorders, tooth wear and sleep disorders, make bruxism an intriguing phenomenon for health professionals. Although the exact cause of bruxism is not fully understood, factors such as stress, anxiety, malocclusion and neurological abnormalities are associated with its manifestation. Accurate diagnosis and an appropriate therapeutic approach are fundamental to its management, including behavioral therapies, oral devices and, in some cases, pharmacological interventions. In-depth research into bruxism is crucial to mitigating its adverse impacts on the oral health and general well-being of affected individuals. Therefore, the objective of this narrative literature review study is to investigate the potential use of botulinum toxin as an adjuvant treatment in orofacial harmonization.